2013
DOI: 10.11120/ndir.2013.00012
|View full text |Cite
|
Sign up to set email alerts
|

Can I Have a Word Please – Strategies to Enhance Understanding of Subject Specific Language in Chemistry by International and Non-traditional Students

Abstract: S. (2013) 'Can I have a word please Strategies to enhance understanding of subject specic language in chemistry by international and non-traditional students.', New directions., 9 (1). pp. 8-13. Further information on publisher's website:http://dx.doi.org/10.11120/ndir.2013.00012Publisher's copyright statement:Additional information: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Word cards are employed to teach technical vocabulary (Coxhead, 2000). Visual aids were regarded as the most useful by the 35 participants in Durham University's Foundation Centre (Bruce et al, 2013). Teachers can raise learners' awareness of technical vocabulary (Coxhead, 2000).…”
Section: Instructional Strategies On Technical Vocabularymentioning
confidence: 99%
See 2 more Smart Citations
“…Word cards are employed to teach technical vocabulary (Coxhead, 2000). Visual aids were regarded as the most useful by the 35 participants in Durham University's Foundation Centre (Bruce et al, 2013). Teachers can raise learners' awareness of technical vocabulary (Coxhead, 2000).…”
Section: Instructional Strategies On Technical Vocabularymentioning
confidence: 99%
“…The empirical studies investigated technical vocabulary instruction in English as Specific Purposes (ESP) in different content areas, including chemistry (i.e., Bruce et al, 2013), hospitality (i.e., Hou, 2014); accounting and finance (i.e., Smith, 2015a), agronomy (i.e., Arno-Macia & Mancho-Bares, 2015); law (i.e., Arno-Macia & Mancho-Bares, 2015) or academic writing (i.e., Brun-Mercer & Zimmerman, 2015;Charles, 2012;Chi, 2010;Zhu & Flaitz, 2005). The empirical studies (e.g., Arno-Macia & Mancho-Bares, 2015) concluded that it is important for learners to acquire technical vocabulary for gaining disciplinary writing improving academic writing.…”
Section: Research Gapmentioning
confidence: 99%
See 1 more Smart Citation
“…Staged reading comprehension activities to develop analytical reading Wellington and Osborne [28] Rules of inference Developing understanding of information that can be inferred such as from chemical equations Herron [35] 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 modelling of atomic structures using classroom materials and via computer simulations. [33] Meanings of words with high demand in the similarity and multiple context dimensions can be taught by provision of opportunities to practise word usage. These include word games, dialogical approaches and peer feedback.…”
Section: Scaffolding Activitiesmentioning
confidence: 99%
“…As a consequence, we have undertaken work to develop pedagogical strategies that will assist students to develop their understanding of the language of chemistry. Initial work to assist students with vocabulary issues involved developing a suite of activities including a student generated online glossary (Rees et al 2013). In this article we describe the development of the FOCUS project (www.dur.…”
Section: Introductionmentioning
confidence: 99%